A Case for Antibodies as Mechanistic Correlates of Immunity in Tuberculosis - Kawahara, Jeffrey Y.; Irvine, Edward B.; Alter, Galit (Frontiers in Immunology, 2019)
Tuberculosis infects one quarter of the world’s population and is the leading cause of death by a single infectious agent, responsible for a reported 1.3 million deaths in 2017. While Mycobacterium tuberculosis is treatable with antibiotic therapy, the increased prevalence of drug resistance, coupled with the variable efficacy of the only widely approved vaccine, has highlighted the need for creative approaches to therapeutic and vaccine development. Historically, a productive immune response to M. tuberculosis has been thought to be nearly entirely cell-mediated, with humoral immunity being largely dismissed. However, in this review, we will discuss the historical skepticism surrounding the role of the humoral immune response to M. tuberculosis, and examine more recent evidence suggesting that antibodies may play a valuable role in host defense against the pathogen. Despite the amount of data portraying antibodies in a negative light, emerging data have begun to highlight the unexpected role of antibodies in M. tuberculosis control. Specifically, it has become clear that antibody features of both the variable and constant domain (Fc) ultimately determine the extent to which antibodies modulate disease. Thus, a more precise definition of the antigen-binding and innate immune recruiting functions of antibodies that contribute to M. tuberculosis restriction, are sure to help guide the development of next-generation therapeutics and vaccines to curb this global epidemic.